Plus-strand strong-stop DNA synthesis in retrotransposon Ty1. - Lauermann, V (1995)
Reverse transcription in the yeast retrotransposon Ty1 follows the general "rules" of retroviral replication overall. However, some details of the retroviral and Ty1 reverse transcription processes are different. We have identified and determined the structure of plus-strand strong-stop DNA and examined the effect of polypurine tract deletion mutations on its synthesis. Furthermore, we have defined the stop signal for plus-strand strong-stop DNA synthesis as an unusual 2'-O-ribosylated nucleotide in the primer tRNA. Full-length plus-strand strong-stop DNA, following strand transfer, would have a terminal 2-base mismatch with minus-strand DNA. These findings indicate that the mechanism of plus-strand strong-stop DNA transfer in Ty1 differs from that of the retroviral transfer and suggest that full-length plus-strand strong-stop DNA is not a direct intermediate in Ty1 retrotransposition.